Improving oral hygiene in the long-term care of the elderly: a RCT - Zenthöfer, Andreas; Dieke, Reinhard; Dieke, Anke; Wege, Karl-Christian; Rammelsberg, Peter; Hassel, Alexander J. (Community dentistry and oral epidemiology, 2013)
Background oral hygiene and health of the institutionalized elderly are frequently described as inadequate. Objectives This randomized and single-blinded (outcome evaluation) study compared three types of intervention for improving oral hygiene with a control. The purpose was to investigate whether there were any significant differences between the intervention and control groups. Methods One hundred and six participants living in long-term care homes in South-West Germany were recruited and randomly divided into four groups—three therapy groups and one control group. For all three therapy groups, teeth and dentures were cleaned professionally and individual instruction was given. One of these groups was also re-instructed and remotivated by a dentist (n = 27). One also received help from, and was remotivation by, staff educated in dental hygiene (n = 26). The third therapy group was not remotivated after professional cleaning of teeth and dentures (n = 26). For the control group, there was no intervention (n = 23). The main target clinical data were mean plaque (plaque-control record, O'Leary), gingival bleeding (Ainamo/Bay), and denture hygiene indices. For assessment of the difference between being in an intervention group and in a control group, mixed-model analysis for repeated measurements was performed for each main target variable. In addition, target clinical data were evaluated in long-term follow-up after 3 years. Results Compared with controls, denture hygiene, plaque, and gingival bleeding indices were significantly lower in the intervention groups over a twelve-week period (mixed model for repeated measurements; P < 0.023). Estimates of effects between control and each treatment group were comparable among the three therapy groups; however, even though two of the groups received further help and instruction. Long-term follow-up showed that all indices were significantly worse than at the last study recall (P < 0.001). Conclusions Professional cleaning of teeth and dentures, with individual instruction, can be recommended to improve oral hygiene. However, the effect decreases over time and renewal of the intervention is necessary.